Anti-bacterial effect of essential oil from Xanthium strumarium against shiga toxin-producing Escherichia coli - Sharifi-Rad, J; Soufi, L; Ayatollahi, S A M; Iriti, M; Sharifi-Rad, M; Varoni, E M; Shahri, F; Esposito, S; Kuhestani, K; Sharifi-Rad, M (Cellular and Molecular Biology, 2016)
Shiga toxin-producing Escherichia coli (STEC) serotype O157:H7 is one of the most important human pathogenic microorganisms, which can cause life-threatening infections. Xanthium strumarium L. is a plant with anti-bacterial activity against gram-negative and gram-positive bacteria. This study aims to demonstrate in vitro efficacy of the essential oil (EO) extracted from Xanthium strumarium L. against E. coli O157:H7. Using the agar test diffusion, the effect of Xanthium strumarium L. EO (5, 10, 15, 30, 60, and 120 mg/mL) was verified at each of the four different growth phases of E. coli O157:H7. Cell counts of viable cells and colony forming unit (CFU) were determined at regular time points using Breed's method and colony counting method, respectively. No viable cell was detectable after the 1 hour-exposure to X. strumarium EO at 30, 60, and 120 mg/mL concentrations. No bacterial colony was formed after 1 h until the end of the incubation period at 24 h. At lower concentrations, the number of bacteria cells decreased and colonies could be observed only after incubation. At the exponential phase, the EO at 15 mg/mL was only bacteriostatic, while from 30 mg/mL started to be bactericidal. X. strumarium EO antibacterial activity against Shiga toxin-producing E. coli O157:H7 is dependent on EO concentration and physiological state of the microorganisms tested. The best inhibitory activity was achieved during the late exponential and the stationary phases.